The antiviral efficacy of HIV-specific CD8⁺ T-cells to a conserved epitope is heavily dependent on the infecting HIV-1 isolate. - Srinika R F Ranasinghe; Holger B Kramer; Cynthia Wright; Benedikt M Kessler; Katalin di Gleria; Yonghong Zhang; Geraldine M Gillespie; Marie-Eve Blais; Abigail Culshaw; Tica Pichulik; Alison Simmons; Sarah L Rowland-Jones; et al. (PLoS Pathogens)
A major challenge to developing a successful HIV vaccine is the vast diversity of viral sequences, yet it is generally assumed that an epitope conserved between different strains will be recognised by responding T-cells. We examined whether an invariant HLA-B8 restricted Nef₉₀₋₉₇ epitope FL8 shared between five high titre viruses and eight recombinant vaccinia viruses expressing Nef from different viral isolates (clades A-H) could activate antiviral activity in FL8-specific cytotoxic T-lymphocytes (CTL). Surprisingly, despite epitope conservation, we found that CTL antiviral efficacy is dependent on the infecting viral isolate. Only 23% of Nef proteins, expressed by HIV-1 isolates or as recombinant vaccinia-Nef, were optimally recognised by CTL. Recognition of the HIV-1 isolates by CTL was independent of clade-grouping but correlated with virus-specific polymorphisms in the epitope flanking region, which altered immunoproteasomal cleavage resulting in enhanced or impaired epitope generation. The finding that the majority of virus isolates failed to present this conserved epitope highlights the importance of viral variance in CTL epitope flanking regions on the efficiency of antigen processing, which has been considerably underestimated previously. This has important implications for future vaccine design strategies since efficient presentation of conserved viral epitopes is necessary to promote enhanced anti-viral immune responses.